Pengaruh Mekanisme Good Corporate Governance, Financial Distress Terhadap Earning Management dengan Variabel Financial Distress sebagai Mediasi : Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia - Ewanto, Muhammad; Fathoni, Ahmad Fauzan; ', Haryeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of good corporate governance on Earning Management and Financial Distress on mining companies listed on Indonesia Stock Exchange (BEI ) in the year 2009-2011. Variables tested in this study consists of institutional ownership,managerial ownership, the proportion of audit committee and independent commissioners, earningsmanagement and financial distress.The sample was mining companies listed on the Indonesia Stock Exchange ( IDX years 2009-2011). The sample was selected using purposive sampling method and obtained a sample of 28 companies. Hypothesis testing is done using multiple regression analysis.Research shows that good corporate governance affect Earning Management. Institutional Ownership significant negative effect, Managerial Ownership significant negative effect. while the proportion of the Audit Committee and the Board of Commissioners of the Independentinsignificant positive effect on Earnings Management. And also after mediated by the Financial Distress Institutional Ownership, Managerial Ownership, and the positive effect on the audit committee Earning Management. while the proportion of independent Board Of Commissioners negative effect.Keywords : Institutional Ownership, Managerial Ownership, Audit Committee and the Board of Commissioners of the Independent proportion, Earnings Management and Financial Distress